Regulation of protein arginine methyltransferase in osteoporosis: a narrative review - Wen, Ruiming; Huang, Ruiqi; Yang, Mianmian; Yang, Jing; Yi, Xuejie (Frontiers in Cell and Developmental Biology, 2025)
Osteoporosis (OP), a systemic bone disease characterised by increased bone fragility and susceptibility to fracture, is mainly caused by a decline in bone mineral density (BMD) and quality caused by an imbalance between bone formation and resorption. Protein arginine methyltransferases (PRMTs) are epigenetic factors and post-translational modification (PTM) enzymes participating in various biological processes, including mRNA splicing, DNA damage repair, transcriptional regulation, and cell signalling. They act by catalysing the transfer and modification of arginine residues and, thus, have become therapeutic targets for OP. In-depth studies have found that these enzymes also play key roles in bone matrix protein metabolism, skeletal cell proliferation and differentiation, and signal pathway regulation to regulate bone formation, bone resorption balance, or both and jointly maintain bone health and stability. However, the expression changes and mechanisms of action of multiple members of the PRMT family differ in OP. Therefore, this paper discusses the biological functions, mechanisms of action, and influencing factors of PRMTs in OP, which is expected to provide a new understanding of the pathogenesis of OP. Furthermore, we present theoretical support for the development of more precise and effective treatment strategies as well as for further study of the molecular mechanisms of PRMTs.